MENTAL ARİTMETİĞİN ORTAOKUL ÖĞRENCİLERİNİN MATEMATİK DERSİNE YÖNELİK BAŞARI DÜZEYLERİNE ETKİSİ - YAVŞAN, HASRET (Fırat Üniveristesi, 2018)
Mental aritmetiğin ortaokul öğrencilerinin matematik dersine yönelik başarı düzeylerine etkisini belirlemeyi amaçlayan bu araştırma nicel verilere dayalı yarı deneysel desende bir araştırmadır. Yapılan bu araştırmada yurtiçi ve yurtdışı kaynaklar incelenmiştir daha sonra araştırmaya uygun bir problem çözme testi seçilerek öntest,sontest,kalıcılık analizleri incelenerek matematik dersine yönelik başarı düzeylerine olumlu etki ettiği sonucuna varılmıştır. Araştırmanın örneklemi Elazığ ilinden seçilmiştir. 2017-2018 eğitim-öğretim yılının birinci ve ikinci yarı yılında A (Özel Kolej) B (Ortaokul) okulları yedinci sınıflarında 2 aylık süreyle gerçekleştirilmiştir. Deney ve kontrol grubu olmak üzere toplam 24 öğrenciden oluşam birbirleriyle homojen iki grup seçilmiştir ve problem çözme test sonuçlarına göre bağımsız t-testi, bağımlı t-testi, ANOVA, ANCOVA gibi analiz yöntemleriyle incelenmiştir. Yapılan analiz sonuçlarına göre mental aritmetik eğitimi alan grubun matematik dersine yönelik başarılarına etkisinin pozitif yönde olduğu sonucuna varılmıştır. Araştırma genelinde matematik dersinde mental aritmetik uygulamaların yapıldığı deney grubunun puanlarında bir artış olduğu sonucuna ulaşılmıştır.

The aim of this study is to determine the effect of mental arithmetic on students' achievement levels in mathematics course at middle school level. This research is an experimental design study based on quantitative data. Domestic and foreign sources were examined in this research then a problem solving test suitable for the research was selected and the results of the pretest, posttest and persistence analyzes were examined and it was concluded that the success level of the mathematics course was positively affected.The study was conducted in the A (Private College) B (Secondary School) schools located in Elazığ province in the first and second semesters of the 2017-2018 academic year in the seventh grades for 2 months. A total of 24 students were selected as homogeneous groups and the results were analyzed by independent t-test, dependent t-test, ANOVA and ANCOVA according to the results of the problem solving test. In the study, mathematics problem solving test was used as a data collection tool to measure students' problem solving abilities. According to the results of the analysis made, it was concluded that the group of the mental arithmetic education group had positive effects on the achievements of the mathematics lesson.It has been concluded that there is an increase in the scores of the experimental group in which the mental arithmetic applications are performed in the mathematics course in general.
The effect of mental architecture on secondary school students to mathematic course for success levels
Keywords: Matematik